Indeks Massa Tubuh dan Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe 2 - Munadia Munadia; Hilman Syarif; Cut Husna (Jurnal Keperawatan Silampari, 2023)
This study aims to determine body mass index and blood sugar levels in patients with type 2 diabetes mellitus in Central Aceh. This research method is a quantitative study with a cross-sectional design. The results showed that the average age of the respondents was 57 years, the majority were women (66.7%), 71.9% had an average body mass index, and 55.2% had high blood sugar levels. In conclusion, managing and implementing the four pillars of diabetes mellitus can be used as a routine agenda in health services. Keywords: Diabetes Mellitus, Education, Body Mass Index, Blood Sugar Levels, Obesity